Slovenski otroci so med telesno najbolj dejavnimi na svetu - Sember, Vedrana (Šport (Ljubljana), 2017)
Increasing physical activity of children and adolescents and reduction of related health risk factors is one of the pressing problems of modern society. With the aim to raise physical activity and health of Slovenian children and adolescents, Slovenia and other developed countries measure their outcomes. Slovenia joined the World Active Initiative Kids Global Alliance in 2016 to monitor policy measures to increase the physical activity of children and adolescents. A group of Slovenian experts prepared a Report for Slovenia 2016 in international comparison Global Matrix 2.0. In this global analysis, 38 countries from 6 continents participated (representing 60% of the world's population). All countries assessed physical activity according to nine indicators following the uniform methodology: Overall physical activity; Organized sport participation; Active play; Active transport;Sedentary behaviours; Family and peers; School, Community and built environment and Government strategies and investments. The average estimates of all indicators were highest in Denmark, Slovenia and the Netherlands. Slovenia performed the best in the indicator of the school with the highest possible grade A and in the Overall physical activity with grade A-. The lowest rated indicator for Slovenia was Active play (grade D), while for Family and peers and the Community and the Built environment we did not report grade du to lack of the information.
Keywords: adolescents; children; javno zdravje; mladina; otroci; physical activity; politics; politika; public health; SLOfit; sport; šport; športna vzgoja; športnovzgojni karton; telesna dejavnost